Isotherms and Kinetic Studies on the Adsorption of Cd(II) onto Activated Carbon Prepared from Coconut (Cocos nucifera) Shell - Shrestha, Rajeshwar Man; Joshi, Sahira (Journal of Nepal Chemical Society, 2019)
Activated carbon prepared coconut shell using Phosphoric acid as an activating agent was investigated to find the feasibility ofits application for removal of Cd(II) from aqueous solution through the adsorption process. The activated carbon thus prepared has been characterized by SEM, XRD, FTIR. SEM morphology has revealed the pores of different diameters while FTIR showed the presence of surface functional groups such as carboxyl, phenolic and lactones. Batch mode kinetics and isotherm studies were carried out to evaluate the effects of contact time, adsorbent dose and pH. The optimum pH, contact time and adsorbent dose needed for the adsorption of the heavy metal have been found to be 6, 180 minutes and 2 g/L respectively. Langmuir and Freundlich isotherm models have been employed to analyze the adsorption equilibrium data. It was found that the adsorption isotherm of Cd(II) onto the activated carbon was the best described by Langmuir with an adsorption capacity of 33.71 mg/g. Kinetic studies showed that a pseudo second-order model was more suitable than the pseudo first-order model. It has been concluded that the activated carbon prepared from coconut shell can be used as an effective adsorbent for the removal of Cd(II) from aqueous solution.